Juridical Analysis of the Application of Restorative Justice in Corruption Crimes in Indonesia - Franata, Hugo S; Santiago, Faisal (Journal of World Science, 2023)
Corruption in Indonesia is still a severe problem and difficult to overcome. Therefore, an adequate alternative solution is needed in dealing with criminal corruption in Indonesia. One such alternative is the application of restorative justice. This study aims to conduct a juridical analysis of the application of restorative justice in acts of corruption in Indonesia, considering the legal principles in force in IndonesiaThe research method used is the normative legal research method. The data sources used are statutory documents, documents related to restorative justice, and legal literature about criminal acts of corruption and restorative justice. The study results are that estorative justice can be a valuable approach in handling corruption cases in Indonesia, but it cannot replace criminal justice processes and criminal sanctions. The research highlights the potential of restorative justice as an alternative, but it also emphasizes the need to overcome implementation challenges and evaluate and monitor its application strictly. This can help restorative justice make a positive contribution to the fight against corruption in Indonesia. Restorative justice can be a useful alternative in handling corruption cases in Indonesia, it cannot replace the criminal justice process and the imposition of criminal sanctions. To make it effective, the challenges in its implementation need to be addressed, and there should be strict evaluation and monitoring to ensure its positive impact in the fight against corruption in Indonesia.